Protective Role of Zinc Picolinate on Cisplatin-Induced Nephrotoxicity in Rats - Tuzcu, Mehmet; Şahin, Nurhan; Dogukan, Ayhan; Aslan, Abdullah; Gencoglu, Hasan; Ilhan, Necip; Şahin, Kazım (W B Saunders Co-Elsevier Inc, 2010)
Objective: Cisplatin-induced nephrotoxicity is related to an increase in lipid peroxidation, oxygen-free radicals, and inflammation in kidney. Zinc is an antioxidant and has anti-inflammatory action. To date, the protective role of zinc picolinate on cisplatin-induced renal injury has not been investigated. The purpose of the present study was to examine the effect of zinc picolinate on cisplatin-induced renal injury. Methods: Male Wistar rats (n = 28, 8-week-old, weighing 200 to 220 g) were divided into four groups consisting of 7 rats each: control, zinc picolinate (6 mg Zn kg(-1) BWi. p.), cisplatin (7 mg kg(-1) BWi. p., single dose) and cisplatin plus zinc picolinate. Results: A single dose of cisplatin resulted in an increase in malondialdehyde, 8-isoprostane, and tumor necrosis factor-a levels of kidney and significantly deranged renal function (urea-N and creatinine; P < .0001). Zinc picolinate treatment significantly reduced urea-N, creatinine, malondialdehyde, 8-isoprostane, and tumor necrosis factor-a -a levels. Concentration of zinc in kidney was increased significantly after zinc picolinate supplementation; however, Fe and Cu levels did not change. Expression of Bax in kidney increased with cisplatin administration, and this could be prevented by zinc picolinate treatment (P < .001). However, bcl-2 expression did not change by zinc or cisplatin treatment (P > .05). The expression of heat shock proteins 60 and 70 in kidney was increased after cisplatin treatment compared with the levels in the control (P < .01), and this increase could be prevented by the zinc picolinate treatment (P < .05). Conclusions: These results suggest that zinc picolinate may be a potential preventive agent in cisplatin-induced renal injury through decreasing oxidative stress and inflammation. (C) 2010 by the National Kidney Foundation, Inc. All rights reserved.
Keywords: Acute-Renal-Failure; Oxidative Dna-Damage; Heat-Shock-Protein; Hydrogen-Peroxide; Lipid-Peroxidation; Tubular Cells; Nitric-Oxide; Kappa-B; Metallothionein; Supplementation